Enduring Cancer : Life, Death, and Diagnosis in Delhi - Banerjee, Dwaipayan, 1983- (Critical global health., 2020)
"ENDURING CANCER is an ethnography of cancer in Delhi, India, and the efforts of patients, families, physicians, and cancer-care workers to navigate the social and bodily disturbances that accompany the disease. Rather than representing cancer as a sudden breakdown of one's social world, Dwai Banerjee examines how cancer in Delhi-where most of the urban poor receive a diagnosis after the time of curative intervention-operates in an accretive fashion by putting pressure on already fragile social ties, and adding to longer histories of personal, familiar, and social vulnerability. Drawing from his research with two cancer treatment centers, as well as his analysis of Indian cultural production of cancer, Banerjee focuses on three fields in particular-a circumspection of speech about the disease, the problem of cancer pain, and the dangers and possibilities of its aesthetic representation-and how each manages doubts about social relations. Chapter 1 focuses on the concealment of cancer diagnoses and its varied implications. Rather than evidencing a denial or escapism, concealing a cancer diagnosis, for Banerjee, represents the pervasiveness of the subjunctive mood in the experience of cancer in Delhi, in which a continuation of life "as if" cancer is not present allows for individuals to exist where revelation may hold danger. Chapter 2 examines the entanglement of palliative care, conjugality, and cancer by describing how cancer puts pressure on already fraught marital relations. Chapter 3 explores how doctors produce, treat, and research cancer pain, and how cancer pain comes into being where social and biological etiologies of pain intersect. These chapters, in particular, interrogate framings of cancer as a "Western" disease, as well as racialized theories of Indian embodiment and religiosity in which Indian people have a higher threshold for pain. Chapters 4 and 5 examine cultural production of cancer in India in the form of cancer memoirs and films, in which a profusion of speech about cancer-rather than reticence or concealment-can be found. Banerjee analyzes these aesthetic forms-and their polished narratives-and positions them as a way for Indian cultural workers to erase the fragmentation caused by cancer. In the last chapter, Banerjee examines the "endurance as ethical," and argues that livability-not flourishing-is often the aim for those affected by cancer and failed by public health systems. This book will be of interest to students and scholars of cultural and medical anthropology, science studies, and South Asian studies"--